Ferroelectric capacitor and preparation method thereof
Lanthanum-doped hafnium zirconium oxide thin films were prepared by atomic layer deposition, which solved the problem that HZO ferroelectric capacitors could not simultaneously achieve high k-values and strong ferroelectricity. This resulted in low-power operation and high reliability, making them suitable for embedded memory and IoT devices.
Patent Information
- Application Number
- CN202510996151.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-18
- Publication Date
- 2025-10-28
AI Technical Summary
Existing HZO-based ferroelectric capacitors cannot simultaneously achieve high k-values and strong ferroelectricity, and are difficult to meet the needs of low-power applications.
Lanthanum-doped hafnium zirconium oxide films were prepared as ferroelectric layers using atomic layer deposition (ALD). The lanthanum doping concentration was controlled to be less than 1 at%. Lanthanum doping was used to regulate the deformation phase boundary, promoting the synergistic coexistence of the T phase and the O-III phase, and suppressing the appearance of non-functional phases.
It achieves both high k-value and strong ferroelectricity under low electric field, significantly reducing energy consumption and making it suitable for embedded memory and IoT devices.
Smart Images

Figure CN120857519A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of semiconductor device technology, and in particular to a ferroelectric capacitor and its preparation method. Background Technology Among numerous ferroelectric materials, HZO (hafnium zirconium oxide) is widely used in ferroelectric capacitors due to its compatibility with complementary metal-oxide-semiconductor (CMOS) processes, scalable integration, wide bandgap (5-6 eV), and tunable ferroelectric stability. It is well known that HZO has various crystal phase structures, including monoclinic (M-phase), tetragonal (T-phase), and orthorhombic (OI / O-III phases). The T-phase dominates with a high dielectric constant k (k>40), the OI phase supports field-induced polarization, and the O-III phase controls ferroelectric polarization. Currently, it is difficult to synergistically optimize the functions of each phase. For example, single-dimensional optimization methods such as nanolamination commonly used in existing technologies cannot simultaneously stabilize high k values and strong ferroelectricity, and are difficult to meet the requirements of low-power applications. Summary of the Invention
[0002] To address the problem that existing HZO-based ferroelectric capacitors cannot simultaneously achieve high k-values and strong ferroelectricity, and are difficult to meet the needs of low-power applications, this invention provides a ferroelectric capacitor that can operate at low voltage and possesses both ferroelectricity and high k-values, as well as its fabrication method.
[0003] In order to achieve the above object, the present invention adopts the following technical solutions: In a first aspect, the present invention provides a ferroelectric capacitor comprising a bottom electrode, a ferroelectric layer and a top electrode arranged sequentially from bottom to top, wherein the ferroelectric layer is a lanthanum-doped hafnium zirconium oxide thin film prepared by atomic layer deposition, wherein the doping concentration of lanthanum in the lanthanum-doped hafnium zirconium oxide thin film is less than 1 at.
[0004] Furthermore, the lanthanum-doped hafnium zirconium oxide thin film includes an M-layer hafnium zirconium oxide layer and an N-layer lanthanum oxide layer deposited in situ between the hafnium zirconium oxide layers. The single hafnium zirconium oxide layer is formed by a single hafnium zirconium atomic layer deposition cycle, and the single lanthanum oxide layer is formed by a single lanthanum atomic layer deposition cycle. M is an integer between 60 and 100, and N is an integer between 1 and 4.
[0005] Furthermore, the molar ratio of hafnium to zirconium in the hafnium-zirconium oxide layer is 1:1, and a single hafnium-zirconium atomic layer deposition cycle includes one hafnium atomic layer deposition cycle and one zirconium atomic layer deposition cycle.
[0006] Furthermore, the molar ratio of hafnium to zirconium in the hafnium-zirconium oxide layer is 2:1, and a single hafnium-zirconium atomic layer deposition cycle includes two hafnium atomic layer deposition cycles and one zirconium atomic layer deposition cycle.
[0007] Secondly, the present invention provides a method for preparing a ferroelectric capacitor, comprising: A bottom electrode is formed on the substrate; A lanthanum-doped hafnium zirconium oxide thin film was grown on the bottom electrode as a ferroelectric layer using atomic layer deposition (ALD), wherein the doping concentration of lanthanum in the lanthanum-doped hafnium zirconium oxide thin film was less than 1 at%; A top electrode is formed on the lanthanum-doped hafnium zirconium oxide thin film and subjected to rapid thermal annealing.
[0008] Further, a lanthanum-doped hafnium zirconium oxide thin film is grown on the bottom electrode, comprising: M hafnium zirconium oxide layers and N lanthanum oxide layers are deposited in situ on the bottom electrode to form the lanthanum-doped hafnium zirconium oxide thin film. The single hafnium zirconium oxide layer is formed by a single hafnium zirconium atomic layer deposition cycle, and the single lanthanum oxide layer is formed by a single lanthanum atomic layer deposition cycle. M is an integer between 60 and 100, and N is an integer between 1 and 4.
[0009] Furthermore, a single hafnium-zirconium atomic layer deposition cycle includes one hafnium atomic layer deposition cycle and one zirconium atomic layer deposition cycle, so that the molar ratio of hafnium to zirconium in the hafnium-zirconium oxide layer is 1:1.
[0010] Furthermore, a single hafnium-zirconium atomic layer deposition cycle comprises two hafnium atomic layer deposition cycles and one zirconium atomic layer deposition cycle, such that the molar ratio of hafnium to zirconium in the hafnium-zirconium oxide layer is 2:1.
[0011] Furthermore, when growing the lanthanum-doped hafnium zirconium oxide thin film using atomic layer deposition, tetradimethylaminohafnium is used as the hafnium precursor, tetradimethylaminozirconium is used as the zirconium precursor, tris(N,N'-diisopropylmethylammonium)lanthanum is used as the lanthanum precursor, and oxygen plasma is used as the oxygen source.
[0012] Furthermore, the bottom electrode and the top electrode are formed by physical vapor deposition.
[0013] By adopting the above technical solution, the present invention has the following advantages over the prior art: This invention employs atomic layer deposition (ALD) to grow a lanthanum-doped hafnium zirconium oxide (HZO) film as a ferroelectric layer on the bottom electrode. This allows for precise control of the lanthanum doping concentration in the HZO film to be less than 1 at%, thus avoiding excessive lanthanum doping that could interfere with crystallization. Furthermore, lanthanum doping regulates the deformation phase boundary (MPB), promoting the synergistic coexistence of the T phase and the O-III phases, thereby achieving a balance between high k-value and strong ferroelectricity. Simultaneously, it suppresses non-functional phases (such as the monoclinic M phase). Moreover, the ferroelectric capacitor of this invention can operate under low electric fields, significantly reducing energy consumption and making it suitable for embedded memory and IoT devices. Attached Figure Description
[0014] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0015] Figure 1 This is a schematic diagram of the ferroelectric capacitor in this invention; Figure 2A This is a schematic diagram of the structure formed after the bottom electrode is grown on the substrate according to the present invention; Figure 2B This is a schematic diagram of the structure formed after growing a lanthanum-doped hafnium zirconium oxide thin film on the bottom electrode according to the present invention; Figure 2C This is a schematic diagram of the structure formed after growing the top electrode on a lanthanum-doped hafnium zirconium oxide thin film according to the present invention; Figure 3A The initial polarization-electric field curves of Embodiments 1-3 and the comparative examples of the present invention are shown below; Figure 3B The initial capacitance-electric field curves of Embodiments 1-3 and the comparative examples of the present invention are shown below; Figure 3C The current density-scan voltage characteristic graphs of Embodiments 1-3 and the comparative examples of the present invention are shown below; Figure 3D These are polarization durability characteristic diagrams of Examples 1-3 and Comparative Examples of the present invention; Figure 3E The following are polarization-electric field curves after wake-up for Embodiments 1-3 and the comparative examples of the present invention; Figure 3F The following are the capacitance-electric field curves after wake-up of Embodiments 1-3 and the comparative examples of the present invention; Figure 4A The following are polarization-electric field curves after wake-up under different voltages in Embodiment 1 of the present invention; Figure 4B This is a diagram showing the capacitance-electric field curves after wake-up at different voltages in Embodiment 1 of the present invention. Figure 4C The following are capacitance-electric field curves after wake-up at different frequencies according to Embodiment 1 of the present invention; Figure 4D The diagram shows the polarization durability characteristics of Embodiment 1 of the present invention under different voltages. Figure 4E This is a durability characteristic diagram of the K value under different voltages for Embodiment 1 of the present invention. Detailed Implementation
[0016] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0017] The terminology used in this invention is for the purpose of describing particular embodiments only and is not intended to be limiting of this disclosure. The singular forms “a,” “the,” and “the” as used in this disclosure and the appended claims are also intended to include the plural forms unless the context clearly indicates otherwise. It should also be understood that the term “and / or” as used herein refers to and includes any and all possible combinations of one or more of the associated listed items.
[0018] As mentioned earlier, existing HZO-based ferroelectric capacitors cannot simultaneously achieve high k-values and strong ferroelectricity, and are difficult to meet the needs of low-power applications. The inventors discovered that La (lanthanum) doping can increase the k-value and reduce the coercive field (Ec), but improper concentration control can disrupt the crystallization process, leading to a decrease in dielectric (DE) and ferroelectric (FE) properties.
[0019] Therefore, the present invention provides a ferroelectric capacitor that can operate at low voltage and possesses both ferroelectricity and a high k-value. For example... Figure 1 As shown, the ferroelectric capacitor includes a bottom electrode 10, a ferroelectric layer 20, and a top electrode 30 arranged sequentially from bottom to top. The ferroelectric layer 20 is a lanthanum-doped hafnium zirconium oxide thin film (denoted as La:HZO or HZxL, where x is the total number of lanthanum atomic layer deposition cycles in the film) prepared by atomic layer deposition, and the doping concentration of lanthanum in the lanthanum-doped hafnium zirconium oxide thin film is less than 1 at%, where at% refers to the atomic percentage, that is, the percentage of lanthanum atoms in the total number of atoms in the film.
[0020] This invention introduces a low dose of lanthanum doping in situ. A lanthanum-doped hafnium zirconium oxide film is grown on the bottom electrode 10 using atomic layer deposition (ALD) as the ferroelectric layer 20. This allows for precise control of the lanthanum doping concentration in the lanthanum-doped hafnium zirconium oxide film to be less than 1 at%. This avoids excessive lanthanum doping that could interfere with crystallization, while also regulating the deformation phase boundary (MPB) through lanthanum doping, promoting the synergistic coexistence of the T phase and the O-III phases, and suppressing non-functional phases (such as the monoclinic M phase). Consequently, the ferroelectric capacitor of this invention achieves a high k-value (approximately 56.2) and strong ferroelectricity (remanent polarization 2Pr approximately 43.4 μC / cm²) under low electric fields (e.g., 1.5 MV / cm), significantly reducing the operating voltage (Vop) and suppressing the "wake-up" effect of traditional HZO, thus improving the reliability and stability of the ferroelectric performance.
[0021] In one embodiment, the lanthanum-doped hafnium zirconium oxide thin film includes stacked M-layer hafnium zirconium oxide (HZO) layers 21 and N-layer lanthanum oxide (La2O3) layers 22. The single-layer hafnium zirconium oxide layer 21 is formed through a single hafnium zirconium atomic layer deposition cycle, and the single-layer lanthanum oxide layer 22 is formed through a single lanthanum atomic layer deposition cycle. M is an integer between 60 and 100, and N is an integer between 1 and 4, with N being optimally 1. When N is greater than 1, the N-layer lanthanum oxide layers can be adjacent to or spaced apart between the hafnium zirconium oxide layers. Preferably, the N-layer lanthanum oxide layer 22 is located in the middle of the lanthanum-doped hafnium zirconium oxide thin film or is uniformly distributed within it. However, this embodiment does not specifically limit its position within the film, as long as the doping concentration of lanthanum in the lanthanum-doped hafnium zirconium oxide thin film is controlled to be less than 1 at%.
[0022] For example, in one embodiment, the lanthanum-doped hafnium zirconium oxide thin film includes 60 stacked hafnium zirconium oxide layers 21 and 1 lanthanum oxide layer 22, the lanthanum oxide layer 22 being deposited in the center of the film, that is, first 30 hafnium zirconium oxide layers 21 are deposited in situ, then 1 lanthanum oxide layer 22 is deposited, and then another 30 hafnium zirconium oxide layers 22 are deposited.
[0023] For example, in another embodiment, the lanthanum-doped hafnium zirconium oxide thin film includes 100 stacked hafnium zirconium oxide layers 21 and 4 lanthanum oxide layers 22, the 4 lanthanum oxide layers 22 being uniformly distributed in the film. That is, after every 20 hafnium zirconium oxide layers 21 are deposited, a lanthanum oxide layer 22 is deposited, and this process is repeated 4 times, and finally the top 20 hafnium zirconium oxide layers 21 are deposited.
[0024] For example, in another embodiment, the lanthanum-doped hafnium zirconium oxide thin film includes 90 stacked hafnium zirconium oxide layers 21 and 2 lanthanum oxide layers 22, which are uniformly distributed in the film. That is, after every 30 hafnium zirconium oxide layers 21 are deposited, a lanthanum oxide layer 22 is deposited, and this process is repeated twice, and finally the top 30 hafnium zirconium oxide layers 21 are deposited.
[0025] In one embodiment, the molar ratio of hafnium (Hf) to zirconium (Zr) in the hafnium-zirconium oxide layer 21 is 1:1, and a single hafnium-zirconium atomic layer deposition cycle includes one hafnium atomic layer deposition cycle and one zirconium atomic layer deposition cycle. This embodiment achieves an optimal balance between high k-value and strong ferroelectricity.
[0026] In another embodiment, the molar ratio of hafnium to zirconium in the hafnium-zirconium oxide layer 21 is 2:1, and a single hafnium-zirconium atomic layer deposition cycle includes two hafnium atomic layer deposition cycles and one zirconium atomic layer deposition cycle. Compared to the previous embodiment, this embodiment still has a high K value, while the ferroelectricity is slightly reduced.
[0027] In one feasible embodiment, the material of the bottom electrode 10 includes, but is not limited to, TiN (titanium nitride), TaN (tantalum nitride), Pt (platinum), W (tungsten), Ru (ruthenium), RuO2 (ruthenium oxide), Pd (palladium), or IrO2 (iridium oxide); the material of the top electrode 30 also includes, but is not limited to, TiN, TaN, Pt, W, Ru, RuO2, Pd, or IrO2. Preferably, both the bottom electrode 10 and the top electrode 30 are made of TiN.
[0028] Another aspect of the present invention provides a method for preparing the aforementioned ferroelectric capacitor, the method specifically comprising the following steps: Step S1, as follows Figure 2A As shown, a bottom electrode 10 is formed on a substrate 100.
[0029] In this invention, the metal bottom electrode 10 can be deposited using physical vapor deposition (e.g., magnetron sputtering). Before deposition, the substrate 100 needs to be cleaned and dried with N2.
[0030] The substrate 100 can be a SiO2 substrate or a Si substrate, etc., and the thickness of the bottom electrode 10 is about 20~100nm.
[0031] Step S2, as follows Figure 2B As shown, a lanthanum-doped hafnium zirconium oxide thin film was co-deposited in situ on the bottom electrode 10 as the ferroelectric layer 20 using atomic layer deposition (ALD). The doping concentration of lanthanum in the lanthanum-doped hafnium zirconium oxide thin film was less than 1 at%.
[0032] Step S3, as follows Figure 2C As shown, a top electrode 30 is formed on a lanthanum-doped hafnium zirconium oxide thin film, thereby obtaining a ferroelectric capacitor structure.
[0033] In this invention, the metal top electrode 30 can be deposited by physical vapor deposition (such as magnetron sputtering), wherein the thickness of the top electrode 300 is about 20~100nm.
[0034] Step S4: Perform rapid thermal annealing (RTA) on the ferroelectric capacitor obtained above. Utilize the principle that the thermal expansion coefficients of the electrodes and the high-k thin film HZO are different to crystallize the HZO thin film and generate ferroelectric orthogonal structures.
[0035] In step S2, this invention employs atomic layer deposition to grow a lanthanum-doped hafnium zirconium oxide thin film in situ on the bottom electrode 10 as a ferroelectric layer 20, precisely controlling the lanthanum doping concentration in the film to be less than 1 at%, thereby enabling the fabrication of a ferroelectric capacitor capable of low-voltage operation and possessing both ferroelectricity and a high k-value. As can be seen, this invention can simultaneously optimize dielectric and ferroelectric properties through a single process step, eliminating the need for complex post-processing such as high-voltage annealing (HPA).
[0036] In one feasible embodiment, step S2 involves in-situ deposition of an M-layer hafnium zirconium oxide layer and an N-layer lanthanum oxide layer on the bottom electrode 10 to form a lanthanum-doped hafnium zirconium oxide thin film. The monolayer hafnium zirconium oxide layer 21 is formed through a single hafnium zirconium atomic layer deposition cycle, and the monolayer lanthanum oxide layer 22 is formed through a single lanthanum atomic layer deposition cycle. M is an integer between 60 and 100, and N is an integer between 1 and 4.
[0037] In one feasible embodiment, step S2 forms a monolayer hafnium-zirconium oxide layer through one hafnium atomic layer deposition cycle and one zirconium atomic layer deposition cycle (i.e., a single hafnium-zirconium atomic layer deposition cycle includes one hafnium atomic layer deposition cycle and one zirconium atomic layer deposition cycle) to obtain a hafnium-zirconium oxide layer with a molar ratio of hafnium (Hf) to zirconium (Zr) of 1:1. It should be understood that one hafnium atomic layer deposition cycle yields one layer of hafnium oxide (HfO2), and one zirconium atomic layer deposition cycle yields one layer of zirconium oxide (ZrO2). Hafnium oxide and zirconium oxide together constitute the hafnium-zirconium oxide layer, as shown below. Figure 1 As shown, green represents the hafnium oxide layer, and blue represents the zirconium oxide layer.
[0038] In another feasible embodiment, step S2 forms a monolayer hafnium-zirconium oxide layer by two hafnium atomic layer deposition cycles and one zirconium atomic layer deposition cycle (i.e., a single hafnium-zirconium atomic layer deposition cycle includes two hafnium atomic layer deposition cycles and one zirconium atomic layer deposition cycle) to obtain a hafnium-zirconium oxide layer with a molar ratio of hafnium (Hf) to zirconium (Zr) of 2:1.
[0039] In one feasible embodiment, in step S2, when growing a lanthanum-doped hafnium zirconium oxide thin film using atomic layer deposition, tetradimethylaminohafnium (TEMAHf) is used as the hafnium precursor, tetradimethylaminozirconium (TEMAZr) is used as the zirconium precursor, tris(N,N'-diisopropylmethylammonium)lanthanum (La-FMD) is used as the lanthanum precursor, oxygen plasma is used as the oxygen source, and the growth process temperature is 250~300℃.
[0040] In one feasible approach, step S4 involves rapid thermal annealing in an inert atmosphere (such as N2 / Ar) at a temperature of 350°C to 500°C to induce crystallization and stabilize the coexistence of the AFE / FE phases. It should be understood that lower annealing temperatures require longer annealing times, and vice versa. For example, at 500°C, the annealing time is 30–60 seconds, while at 350°C, it is approximately 300 seconds.
[0041] Example 1 The method for preparing the ferroelectric capacitor in this embodiment includes the following steps: Step S11: A 50 nm TiN substrate is deposited as the bottom electrode 10 using magnetron sputtering. This bottom electrode 10 has good conductivity, with a sheet resistance of approximately 20 Ω / □ (ohms per square, used to represent the resistance between opposite sides of a square thin film material). After completion, as shown... Figure 2A As shown.
[0042] In step S12, a lanthanum-doped hafnium zirconium oxide thin film is deposited on the bottom electrode 10 as a ferroelectric layer 20 using a plasma-enhanced atomic layer deposition system (PEALD). The deposition process temperature is 250°C. Tetra-dimethylaminohafnium is used as the hafnium precursor, tetra-dimethylaminozirconium is used as the zirconium precursor, tris(N,N'-diisopropylmethylammonium)lanthanum is used as the lanthanum precursor, and oxygen plasma is used as the oxygen source.
[0043] During deposition, firstly, 30 layers of hafnium zirconium oxide 21 (referred to as the lower hafnium zirconium oxide layer) are deposited in situ on the substrate. Then, one layer of lanthanum oxide 22 is deposited in situ on the lower hafnium zirconium oxide layer 21. Finally, another 30 layers of hafnium zirconium oxide 21 (referred to as the upper hafnium zirconium oxide layer) are deposited in situ on the lanthanum oxide layer 22, thus obtaining a lanthanum-doped hafnium zirconium oxide thin film. (The final result is as follows...) Figure 2B As shown. In this embodiment, the monolayer hafnium zirconium oxide layer is formed by alternating between one hafnium atomic layer deposition cycle and one zirconium atomic layer deposition cycle, and the monolayer lanthanum oxide layer is formed by one lanthanum atomic layer deposition cycle. The lanthanum-doped hafnium zirconium oxide film obtained in this embodiment is named HZ1L, and the doping concentration of lanthanum in the lanthanum-doped hafnium zirconium oxide film HZ1L is 0.17 at%.
[0044] Step S13: A 50 nm TiN layer is deposited on a lanthanum-doped hafnium zirconium oxide film using magnetron sputtering as the top electrode 30. This top electrode 30 exhibits good conductivity, with a sheet resistance of approximately 20 Ω / □. The result is as follows: Figure 2C The ferroelectric capacitor shown.
[0045] Step S14: Perform rapid heat treatment on the ferroelectric capacitor at 500°C for 60 seconds.
[0046] Example 2 The method for preparing the ferroelectric capacitor in this embodiment includes the following steps: In step S21, a 50 nm TiN substrate is deposited as a bottom electrode 10 using magnetron sputtering. The bottom electrode 10 has good conductivity and a sheet resistance of about 20 Ω / □.
[0047] In step S22, a lanthanum-doped hafnium zirconium oxide thin film is deposited on the bottom electrode 10 as a ferroelectric layer 20 using a plasma-enhanced atomic layer deposition system (PEALD). The deposition process temperature is 250°C. Tetra-dimethylaminohafnium is used as the hafnium precursor, tetra-dimethylaminozirconium is used as the zirconium precursor, tris(N,N'-diisopropylmethylammonium)lanthanum is used as the lanthanum precursor, and oxygen plasma is used as the oxygen source.
[0048] During deposition, 30 hafnium zirconium oxide layers 21 (referred to as the lower hafnium zirconium oxide layer) are first deposited in situ on the substrate. Then, 3 lanthanum oxide layers 22 are deposited in situ on the lower hafnium zirconium oxide layer 21. Finally, another 30 hafnium zirconium oxide layers 21 (referred to as the upper hafnium zirconium oxide layer) are deposited in situ on the lanthanum oxide layer 21, thus obtaining the lanthanum-doped hafnium zirconium oxide thin film. In this embodiment, the monolayer hafnium zirconium oxide layer is formed by alternating between one hafnium atomic layer deposition cycle and one zirconium atomic layer deposition cycle, and the monolayer lanthanum oxide layer is formed by one lanthanum atomic layer deposition cycle. The lanthanum-doped hafnium zirconium oxide thin film obtained in this embodiment is named HZ3L, and the doping concentration of lanthanum in the lanthanum-doped hafnium zirconium oxide thin film HZ3L is 0.33 at%.
[0049] In step S23, a 50 nm TiN layer is deposited on a lanthanum-doped hafnium zirconium oxide film as the top electrode 30 using magnetron sputtering, thereby obtaining a ferroelectric capacitor. This top electrode 30 exhibits good conductivity, with a sheet resistance of approximately 20 Ω / □.
[0050] Step S24: Perform rapid heat treatment on the ferroelectric capacitor at 500°C for 60 seconds.
[0051] Example 3 The method for preparing the ferroelectric capacitor in this embodiment includes the following steps: In step S31, a 50 nm TiN substrate is deposited as a bottom electrode 10 using magnetron sputtering. The bottom electrode 10 has good conductivity and a sheet resistance of about 20 Ω / □.
[0052] In step S32, a lanthanum-doped hafnium zirconium oxide thin film is deposited on the bottom electrode 10 as a ferroelectric layer 20 using a plasma-enhanced atomic layer deposition system (PEALD). The deposition process temperature is 250°C. Tetra-dimethylaminohafnium is used as the hafnium precursor, tetra-dimethylaminozirconium is used as the zirconium precursor, tris(N,N'-diisopropylmethylammonium)lanthanum is used as the lanthanum precursor, and oxygen plasma is used as the oxygen source.
[0053] During deposition, 30 hafnium zirconium oxide layers 21 (referred to as the lower hafnium zirconium oxide layer) are first deposited in situ on the substrate. Then, 4 lanthanum oxide layers 22 are deposited in situ on the lower hafnium zirconium oxide layer 21. Finally, 30 hafnium zirconium oxide layers (referred to as the upper hafnium zirconium oxide layer) are deposited in situ again on the lanthanum oxide layer 22, thus obtaining the lanthanum-doped hafnium zirconium oxide thin film. In this embodiment, the monolayer hafnium zirconium oxide layer is formed by alternating between one hafnium atomic layer deposition cycle and one zirconium atomic layer deposition cycle, and the monolayer lanthanum oxide layer is formed by one lanthanum atomic layer deposition cycle. The lanthanum-doped hafnium zirconium oxide thin film obtained in this embodiment is named HZ4L, and the doping concentration of lanthanum in the lanthanum-doped hafnium zirconium oxide thin film HZ3L is 0.53 at%.
[0054] In step S33, a 50 nm TiN layer is deposited on a lanthanum-doped hafnium zirconium oxide film as the top electrode 30 using magnetron sputtering, thereby obtaining a ferroelectric capacitor. This top electrode 30 exhibits good conductivity, with a sheet resistance of approximately 20 Ω / □.
[0055] Step S34: Perform rapid heat treatment on the ferroelectric capacitor at 500°C for 60 seconds.
[0056] Comparative Example 1 The method for preparing the ferroelectric capacitor in this comparative example includes the following steps: In step S41, a 50 nm TiN substrate is deposited as a bottom electrode 10 using magnetron sputtering. The bottom electrode 10 has good conductivity and a sheet resistance of about 20 Ω / □.
[0057] In step S42, a lanthanum-doped hafnium zirconium oxide thin film is deposited on the bottom electrode 10 as a ferroelectric layer 20 using a plasma-enhanced atomic layer deposition system (PEALD). The deposition process temperature is 250°C. Tetra-dimethylaminohafnium is used as the hafnium precursor, tetra-dimethylaminozirconium is used as the zirconium precursor, tris(N,N'-diisopropylmethylammonium)lanthanum is used as the lanthanum precursor, and oxygen plasma is used as the oxygen source.
[0058] During deposition, 30 hafnium zirconium oxide layers 21 (referred to as the lower hafnium zirconium oxide layer) are first deposited in situ on the substrate. Then, 7 lanthanum oxide layers 22 are deposited in situ on the lower hafnium zirconium oxide layer 21. Finally, another 30 hafnium zirconium oxide layers 21 (referred to as the upper hafnium zirconium oxide layer) are deposited in situ on the lanthanum oxide layer 22, thus obtaining the lanthanum-doped hafnium zirconium oxide thin film. In this embodiment, the monolayer hafnium zirconium oxide layer is formed by alternating between one hafnium atomic layer deposition cycle and one zirconium atomic layer deposition cycle, and the monolayer lanthanum oxide layer is formed by one lanthanum atomic layer deposition cycle. The lanthanum-doped hafnium zirconium oxide thin film obtained in this embodiment is named HZ7L, and the doping concentration of lanthanum in the lanthanum-doped hafnium zirconium oxide thin film HZ3L is 1.32 at.
[0059] In step S43, a 50 nm TiN layer is deposited on a lanthanum-doped hafnium zirconium oxide film as the top electrode 30 using magnetron sputtering, thereby obtaining a ferroelectric capacitor. This top electrode 30 exhibits good conductivity, with a sheet resistance of approximately 20 Ω / □.
[0060] Step S44: Perform rapid heat treatment on the ferroelectric capacitor at 500°C for 60 seconds.
[0061] As can be seen, the difference between Comparative Example 1 and the aforementioned embodiments is that the lanthanum doping concentration is greater than 1 at.
[0062] Comparative Example 2 The method for preparing the ferroelectric capacitor in this comparative example includes the following steps: In step S51, a 50 nm TiN substrate is deposited as a bottom electrode 10 using magnetron sputtering. The bottom electrode 10 has good conductivity and a sheet resistance of about 20 Ω / □.
[0063] In step S52, a 60-layer hafnium zirconium oxide thin film is deposited on the bottom electrode 10 as a ferroelectric layer 20 (lanthanum doping concentration is 0 at%) using a plasma enhanced atomic layer deposition system (PEALD). The deposition process temperature is 250°C, with tetradimethylaminohafnium as the hafnium precursor, tetradimethylaminozirconium as the zirconium precursor, and oxygen plasma as the oxygen source.
[0064] In this embodiment, a single-layer hafnium-zirconium oxide layer is formed by alternating between one hafnium atomic layer deposition cycle and one zirconium atomic layer deposition cycle. The hafnium-zirconium oxide thin film obtained in this embodiment is named HZO.
[0065] In step S53, a 50 nm TiN layer is deposited on a hafnium zirconium oxide thin film using magnetron sputtering as the top electrode 30, thereby obtaining a ferroelectric capacitor. This top electrode 30 has good conductivity, with a sheet resistance of approximately 20 Ω / □.
[0066] Step S54: Perform rapid heat treatment on the ferroelectric capacitor at 500°C for 60 seconds.
[0067] As can be seen, the difference between Comparative Example 2 and the aforementioned embodiments is that the ferroelectric layer was not doped with lanthanum.
[0068] The present invention conducted electrical tests on the ferroelectric layer 20 of Examples 1-3 and Comparative Examples 1-2, respectively. The test results are shown in [reference needed]. Figures 3A-3F As shown.
[0069] Figure 3A The graphs shown are the initial polarization-electric field curves of Examples 1-3 and the comparative examples of the present invention. The horizontal axis represents the Electric Field (mV / cm), and the vertical axis represents the Polarization (μC / cm). 2 .from Figure 3A It can be seen that the device doped with La according to the embodiments of the present invention has stronger initial ferroelectric properties compared with the comparative example.
[0070] Figure 3B The graphs shown are the initial capacitance-electric field curves for Embodiments 1-3 and the comparative examples of the present invention. The horizontal axis represents the electric field (MV / cm), and the vertical axis represents the dielectric constant. Figure 3B It can be seen that, according to the embodiments of the present invention, the devices doped with 1-cycle La and 3-cycle La have a very high k value at 0V.
[0071] Figure 3CThe current density-sweeping voltage characteristic graphs for Embodiments 1-3 and the comparative examples of the present invention are shown below. The horizontal axis represents Sweeping Voltage (V), and the vertical axis represents Current Density (A / cm). 2 .from Figure 3C It can be seen that, according to the embodiments of the present invention, the device doped with La has a lower leakage current compared to the comparative example at 1.4V.
[0072] Figure 3D The graph shows the polarization durability characteristics of Examples 1-3 and the comparative examples of the present invention. The horizontal axis represents Endurance Cycles (number of pulse cycles), and the vertical axis represents Pr (residual polarization intensity). The unit is μC / cm. 2 .from Figure 3D It can be seen that, according to the embodiments of the present invention, the device doped with La is more resistant to pulse cycles and has higher reliability than the comparative example.
[0073] Figure 3E The graphs shown are polarization-electric field curves after awakening for Examples 1-3 and the comparative examples of the present invention. The horizontal axis represents the Electric Field (MV / cm), and the vertical axis represents the Polarization (μC / cm). 2 .from Figure 3E It can be seen that the device doped with La according to the embodiments of the present invention has stronger ferroelectricity after being awakened.
[0074] Figure 3F The graphs shown are the capacitance-electric field curves after wake-up for Embodiments 1-3 and the comparative examples of the present invention. The horizontal axis represents the electric field (MV / cm), and the vertical axis represents the dielectric constant. Figure 3F It can be seen that the device doped with La according to the embodiments of the present invention has a higher k value after wake-up.
[0075] As can be seen from the above electrical test results, the ferroelectric capacitor according to the embodiment of the present invention has both a high storage window (2Pr) and a dielectric constant (k value).
[0076] The present invention performs electrical tests on the ferroelectric layer 20 of Example 1 under electric field cycling. The test results are shown in [reference]. Figures 4A-4E As shown.
[0077] Figure 4AThe graphs shown are polarization-electric field curves after wake-up at different voltages for Embodiment 1 of the present invention (with Comparative Example 2 as a reference). The horizontal axis represents Electric Field (mV / cm), and the vertical axis represents Polarization (μC / cm). 2 .from Figure 4A It can be seen that the device doped with La in Example 1 has stronger ferroelectricity.
[0078] Figure 4B The graph shows the capacitance-electric field curves after wake-up at different voltages for Embodiment 1 of the present invention (with Comparative Example 2 as a reference). The horizontal axis represents the Electric Field (MV / cm), and the vertical axis represents the dielectric constant. Figure 4B It can be seen that the device doped with La in Example 1 has a higher K value after wake-up.
[0079] Figure 4C The graph shows the capacitance-electric field curves after wake-up at different frequencies for Embodiment 1 of the present invention (with Comparative Example 2 as a reference). The horizontal axis represents the Electric Field, in MV / cm; the vertical axis represents the Dielectric Constant. Figure 4C It can be seen that the device doped with La in Example 1 has a higher k value after wake-up.
[0080] Figure 4D The graph shows the polarization durability characteristics of Embodiment 1 of the present invention under different voltages (with Comparative Example 2 as a reference). The horizontal axis represents Endurance Cycles (number of pulse cycles), and the vertical axis represents Pr (residual polarization intensity). The unit is μC / cm. 2 .from Figure 4D It can be seen that the device doped with La in Example 1 has greater tolerance to pulse cycles and higher reliability.
[0081] Figure 4E This is a graph showing the k-value durability characteristics of Embodiment 1 of the present invention under different voltages (with Comparative Example 2 as a reference). The horizontal axis represents Endurance Cycles, the left vertical axis represents the k-value, and the right vertical axis represents the Equivalent Oxide Thickness (EOT). A lower EOT indicates better gate control capability when the ferroelectric layer is used as the gate. Figure 4E It can be seen that the device doped with La in Example 1 has better durability at high k values.
[0082] It can be seen that the ferroelectric capacitor of Example 1 has high reliability, large 2Pr and high k value under low operating voltage.
[0083] While specific embodiments of the present invention have been described above, those skilled in the art should understand that these are merely illustrative examples, and the scope of protection of the present invention is defined by the appended claims. Those skilled in the art can make various changes or modifications to these embodiments without departing from the principles and essence of the present invention, but all such changes and modifications fall within the scope of protection of the present invention.
Claims
1. A ferroelectric capacitor, comprising a bottom electrode, a ferroelectric layer, and a top electrode arranged sequentially from bottom to top, characterized in that, The ferroelectric layer is a lanthanum-doped hafnium zirconium oxide thin film prepared by atomic layer deposition, wherein the doping concentration of lanthanum in the lanthanum-doped hafnium zirconium oxide thin film is less than 1 at.
2. The ferroelectric capacitor as described in claim 1, characterized in that, The lanthanum-doped hafnium zirconium oxide thin film comprises M stacked hafnium zirconium oxide layers and N stacked lanthanum oxide layers. The single hafnium zirconium oxide layer is formed by a single hafnium zirconium atomic layer deposition cycle, and the single lanthanum oxide layer is formed by a single lanthanum atomic layer deposition cycle. M is an integer between 60 and 100, and N is an integer between 1 and 4.
3. The ferroelectric capacitor as described in claim 2, characterized in that, The molar ratio of hafnium to zirconium in the hafnium-zirconium oxide layer is 1:1, and a single hafnium-zirconium atomic layer deposition cycle includes one hafnium atomic layer deposition cycle and one zirconium atomic layer deposition cycle.
4. The ferroelectric capacitor as described in claim 2, characterized in that, The molar ratio of hafnium to zirconium in the hafnium-zirconium oxide layer is 2:1, and a single hafnium-zirconium atomic layer deposition cycle includes two hafnium atomic layer deposition cycles and one zirconium atomic layer deposition cycle.
5. A method for preparing a ferroelectric capacitor, characterized in that, include: A bottom electrode is formed on the substrate; A lanthanum-doped hafnium zirconium oxide thin film was grown on the bottom electrode as a ferroelectric layer using atomic layer deposition (ALD), wherein the doping concentration of lanthanum in the lanthanum-doped hafnium zirconium oxide thin film was less than 1 at%; A top electrode is formed on the lanthanum-doped hafnium zirconium oxide thin film and subjected to rapid thermal annealing.
6. The preparation method according to claim 5, characterized in that, Growing a lanthanum-doped hafnium zirconium oxide thin film on the bottom electrode includes: M layers of hafnium zirconium oxide and N layers of lanthanum oxide are deposited in situ on the bottom electrode to form the lanthanum-doped hafnium zirconium oxide thin film. The single hafnium zirconium oxide layer is formed by a single hafnium zirconium atomic layer deposition cycle, and the single lanthanum oxide layer is formed by a single lanthanum atomic layer deposition cycle. M is an integer between 60 and 100, and N is an integer between 1 and 4.
7. The preparation method according to claim 6, characterized in that, A single hafnium-zirconium atomic layer deposition cycle comprises one hafnium atomic layer deposition cycle and one zirconium atomic layer deposition cycle, such that the molar ratio of hafnium to zirconium in the hafnium-zirconium oxide layer is 1:
1.
8. The preparation method according to claim 6, characterized in that, A single hafnium-zirconium atomic layer deposition cycle comprises two hafnium atomic layer deposition cycles and one zirconium atomic layer deposition cycle, such that the molar ratio of hafnium to zirconium in the hafnium-zirconium oxide layer is 2:
1.
9. The preparation method according to claim 5, characterized in that, When growing the lanthanum-doped hafnium zirconium oxide thin film using atomic layer deposition, tetradimethylaminohafnium is used as the hafnium precursor, tetradimethylaminozirconium is used as the zirconium precursor, tris(N,N'-diisopropylmethylammonium)lanthanum is used as the lanthanum precursor, and oxygen plasma is used as the oxygen source.
10. The preparation method according to claim 5, characterized in that, The bottom electrode and the top electrode are formed by physical vapor deposition.
Citation Information
Cited By
Ferroelectric capacitor based on morphotropic phase boundary and preparation method and application thereof
CN122205882A